IDIOMS DENOTHING DEATH (ON THE EXAMPLE OF POLISH AND UKRAINIAN FOLK SONGS) - Mycan, D. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The paper treats of comparison of idiomatic expressions in Polish and Ukrainian languages. Analyzed idiomatic items are similar in respect of defining the notion of the death. The main condition is that they include a component – a name of human body. In such a case idiomatic items including components głowa/head, oczy/eyes, szyja/neck, kark/nape, ręka/hand, noga/leg, krew/bload, kości/bones, ciało/body were analyzed.